Open abdomen and entero-atmospheric fistulae: An interim analysis from the International Register of Open Abdomen (IROA). Issue 1 (January 2019) - Coccolini, Federico; Ceresoli, Marco; Kluger, Yoram; Kirkpatrick, Andrew; Montori, Giulia; Salvetti, Fracensco; Fugazzola, Paola; Tomasoni, Matteo; Sartelli, Massimo; Ansaloni, Luca; Catena, Fausto; Negoi, Ionut; et al.
Highlights: Entero-atmospheric fistula developed in 9% of the patients. Techniques for temporary closure did not affect fistula formation. Days of open abdomen, cancer and time to nutrition are related to EAF. Abstract: Introduction: No definitive data describing associations between cases of Open Abdomen (OA) and Entero-atmospheric fistulae (EAF) exist. The World Society of Emergency Surgery (WSES) and the Panamerican Trauma Society (PTS) thus analyzed the International Register of Open Abdomen (IROA) to assess this question. Material and methods: A prospective analysis of adult patients enrolled in the IROA. Results: Among 649 adult patients with OA 58 (8.9%) developed EAF. Indications for OA were peritonitis (51.2%) and traumatic-injury (16.8%). The most frequently utilized temporary abdominal closure techniques were Commercial-NPWT (46.8%) and Bogotà-bag (21.9%). Mean OA days were 7.9 ± 18.22. Overall mortality rate was 29.7%, with EAF having no impact on mortality. Multivariate analysis associated cancer (p = 0.018), days of OA (p = 0.003) and time to provision-of-nutrition (p = 0.016) with EAF occurrence. Conclusion: Entero-atmospheric fistulas are influenced by the duration of open abdomen treatment and by the nutritional status of the patient. Peritonitis, intestinal anastomosis, negative pressure and oral or enteral nutrition were not risk factors for EAF during OA treatment.